A Pragmatic Analysis of Women and Angry Speech: Case Study of The Saudi Arabian Takki Series - Nailah Farafishah; Haeruddin Haeruddin; Ilham Ramadhan; Muhammad Anwar Ahmad (Alsina : Journal of Arabic Studies, 2025)
This study aims to reveal the forms of illocutionary acts and impoliteness strategies in anger utterances directed at women in the Saudi Arabian series Takki. In Arab culture, angry utterances are not merely emotional expressions but serve as tools for enforcing social norms and patriarchal control. This research employs a descriptive qualitative method with a pragmatic approach. The data, consisting of dialogue excerpts, were analyzed using Searle's speech act theory and Culpeper's theory of impoliteness. The results show that anger utterances in Takki are dominated by directive, expressive, commissive, and declarative acts, accompanied by impoliteness strategies, including insults, prohibitions, threats, and verbal abuse. These utterances reflect unequal power relations between men and women and reinforce patriarchal structures in Saudi society. This study confirms that language functions as a significant tool of social control in cultures where family honor is paramount. By uncovering the pragmatic mechanisms that sustain gendered communication hierarchies, this research contributes to the broader understanding of how linguistic behavior reinforces social ideologies within both pragmatic and sociocultural theoretical frameworks.